The Risks in Agriculture, Farmers' Responses and Support Solutions in Nghe An - Van Thi Thuy Hoang (Journal of Development Research, 2021)
This study focuses on analyzing the risks that affect in agricultural production and response of farmers. Research data was collected in Nghe An, Vietnam with 200 samples, audited by Binary Logistic Model. The research results show that the main risks affecting agriculture in Nghe An are mainly weather risks, pest risks and economic risks. And to cope with those risks, farmers have chosen a number of response measures, based on the support of the government, that have yielded clear results. The study provides empirical evidence on the current situation of risk identification and how to choose to respond to risks in agriculture, offering solutions to help improve the agricultural risk management framework in Nghe An, Vietnam.